Obesity and Hypertension in School Children of Puerto Rico - Santiago, Héctor; Pagán, Damaris; Acevedo, Ariette (Puerto Rico Health Sciences Journal, 2021)
Objective: To determine the prevalence of obesity and hypertension and the association of hypertension with obesity in an island-wide sample of school children in Puerto Rico. Methods: The quantitative descriptive study included 3,145 children, 5 to 17 years of age, from Puerto Rico; they were examined once during a 3-year (2014−2017) period for weight (lbs) and height (cm) to calculate their body mass index (BMI) based on their age and sex. Children with BMIs in or above the 95th percentile were considered obese. The systolic and diastolic blood pressures (mm Hg) were measured once to determine the prevalence of hypertension based on age, height, and sex. Children with blood pressures in or above the 95th percentile were considered hypertensive. The blood pressures of obese and non-obese children were compared using the independent samples t-test. The association between obesity status (obese/non-obese) and hypertensive status (hypertensive/non hypertensive) was analyzed using the chi-square test. Results: A total of 25.7% of the children were obese. Boys were 1.38 times as likely to be obese as girls were. 9.9% of the children were hypertensive. Obese children were 2.82 times as likely to be hypertensive as non-obese children were. Conclusion: About 1 of every 4 children in the sample was obese; about 1 of 10 was hypertensive. Obese children were at a significantly higher risk for hypertension than non-obese children were. The study indicates the need for public health strategies that promote prevention and parental education to reduce the prevalence of obesity and the sequelae of hypertension.